Globalisation, environment and social justice : perspectives, issues and concerns - Manish K Verma,Ed (Routledge, 2019)
This volume provides a comprehensive account of the connections between globalisation, environment and social justice. It examines varied dimensions of environmental sustainability; the adverse impact of globalisation on environment and its consequences for poverty, unemployment and displacement; the impacts on marginalised sections such as scheduled castes and tribes and women; and policy frameworks for ensuring environmental sustainability and social justice.